2017
DOI: 10.1080/17482798.2017.1386580
|View full text |Cite
|
Sign up to set email alerts
|

Shall I call, text, post it online or just tell it face-to-face? How and why Flemish adolescents choose to share their emotions on- or offline

Abstract: Social sharing of emotions is a frequently used emotion regulation strategy. This study adds to the emotion regulation literature and the affordances of technologies perspective by providing a better understanding of with whom adolescents share emotions on-and offline, how they do this and why they use certain modes. In-depth interviews with 22 Flemish adolescents (aged 14-18) show that these youngsters share almost all experienced emotions, often with multiple recipients and using multiple communication modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Thus, it is possible that this finding reflects the preferences of younger adolescents for communicating with their friends in-person rather than by text. However, given the limitations of online support identified by the girls in this study, this preference for in-person sources of support suggests that adolescents recognise clear benefits of seeking support in-person (Frison & Eggermont, 2015;Vermeulen et al, 2018a). The preference for seeking support in-person also aligns with the preferences of college students, who are more likely to seek support in-person rather than by text message or online (Rife et al, 2016) and identify that in-person exchanges are more supportive than those received via text-messaging or social media (Bayer et al, 2016).…”
Section: Preferred Mode Of Support Seekingmentioning
confidence: 86%
See 4 more Smart Citations
“…Thus, it is possible that this finding reflects the preferences of younger adolescents for communicating with their friends in-person rather than by text. However, given the limitations of online support identified by the girls in this study, this preference for in-person sources of support suggests that adolescents recognise clear benefits of seeking support in-person (Frison & Eggermont, 2015;Vermeulen et al, 2018a). The preference for seeking support in-person also aligns with the preferences of college students, who are more likely to seek support in-person rather than by text message or online (Rife et al, 2016) and identify that in-person exchanges are more supportive than those received via text-messaging or social media (Bayer et al, 2016).…”
Section: Preferred Mode Of Support Seekingmentioning
confidence: 86%
“…Similarly, Rains et al (2017) found that college students who received support via IMing experienced higher levels of uncertainty and worry than those who received the same support in-person in an experimental study. Finally, in recent work by Vermeulen et al (2018a), Flemish adolescents identified that they preferred to share emotions face-to-face rather than online. This was because they could see the reactions of their friends and clarify misunderstandings.…”
Section: Potential Limitations For Adolescent Girls Seeking Support Umentioning
confidence: 92%
See 3 more Smart Citations